2011
DOI: 10.4081/hi.2011.e2
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition as Assessed by Nutritional Risk Index is Associated with Worse Outcome in Patients Admitted with Acute Decompensated Heart Failure: An ACAP-HF Data Analysis

Abstract: Malnutrition is common at hospital admission and tends to worsen during hospitalization. This controlled population study aimed to determine if serum albumin or moderate and severe nutritional depletion by Nutritional Risk Index (NRI) at hospital admission are associated with increased length of hospital stay (LOS) in patients admitted with acute decompensated heart failure (ADHF). Serum albumin levels and lymphocyte counts were retrospectively determined at hospital admission in 1740 consecutive patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 45 publications
4
87
1
1
Order By: Relevance
“…The prevalence of malnutrition and frailty in our cohort was around 45% and 50% respectively, similar to findings from other studies (34% to 70% 6, 26,27 for malnutrition and 30% to 50% 28 for frailty). Ours is the first paper to compare directly several different indices of malnutrition and frailty in patients hospitalised with HF.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of malnutrition and frailty in our cohort was around 45% and 50% respectively, similar to findings from other studies (34% to 70% 6, 26,27 for malnutrition and 30% to 50% 28 for frailty). Ours is the first paper to compare directly several different indices of malnutrition and frailty in patients hospitalised with HF.…”
Section: Discussionsupporting
confidence: 80%
“…The Nutritional Risk Index (NRI), an easily calculated measure that incorporates albumin and body size, predicts mortality in single-center cohorts of ambulatory 12 and hospitalized 13 HF patients. The impact of NRI on mortality risk in advanced HF is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Considering such a counteracting effect, GNRI as a combined index of albumin and BMI may lead to minimization of the effect of fluid status, and identify nutritional risk better than each of them. 13 indicating that GNRI had the highest predictive value for predicting mortality ( Table 3).…”
Section: Patient Characteristics According To Gnrimentioning
confidence: 99%
“…Aziz et al reported that NRI was associated with the composite endpoints all-cause mortality and HF readmission in patients with acute decompensated HF. 13 Al-Najjar and Clark have also shown that NRI predicts mortality in outpatients with HFrEF. 14 We have further extended previous findings by demonstrating the clinical significance of the GNRI, a modified NRI, in HFpEF patients for the first time.…”
mentioning
confidence: 99%